Eosinophil-Derived Osteopontin Induces the Expression of Pro-Inflammatory Mediators and Stimulates Extracellular Matrix Production in Nasal Fibroblasts: The Role of Osteopontin in Eosinophilic Chronic Rhinosinusitis - Yang, Hyun-Woo; Park, Joo-Hoo; Jo, Min-Sik; Shin, Jae-Min; Kim, Dae Woo; Park, Il-Ho (Frontiers in Immunology, 2022)
Background: Eosinophilic chronic rhinosinusitis (ECRS) is a subtype of chronic rhinosinusitis (CRS) and is a refractory or intractable disease. However, a reliable clinical marker or an effective treatment strategy has not yet been established. ECRS is accompanied by excessive eosinophil infiltration and Th2 inflammatory response, which is closely related to tissue remodeling in the upper airways. Objectives: We sought to investigate the effect of eosinophils on tissue remodeling in ECRS. The purpose of this study was to identify the effects of eosinophils on the expression of pro-inflammatory mediators and extracellular matrix (ECM) in nasal fibroblasts and the key mediators that stimulate them. Methods: Butyric acid was used to differentiate EOL-1 cells into eosinophils. We co-cultured differentiated EOL-1 cells and fibroblasts to measure the expression of pro-inflammatory mediators and ECM in fibroblasts. Among the cytokines secreted from the differentiated EOL-1 cells, factors that induced tissue remodeling of fibroblasts were identified. Results: Treatment with butyric acid (BA) differentiated EOL-1 cells into eosinophils. Differentiated EOL-1 cells induced fibroblasts to produce pro-inflammatory mediators, IL-6 and IL-8, and tissue remodeling factor, VEGF. It also induced myofibroblast differentiation and overexpression of ECM components. Differentiated EOL-1 cells overexpressed osteopontin (OPN), and recombinant OPN increased the expression of IL-6, IL-8, VEGF, and ECM components in nasal fibroblast. OPN was overexpressed in the nasal tissue of patients with ECRS and was associated with the severity of CRS. Conclusions: Eosinophil-derived OPN stimulated nasal fibroblasts and contributed to inflammation and tissue remodeling in ECRS. Moreover, the expression level of OPN was proportional to the severity of ECRS. Therefore, OPN regulation is a potential treatment for ECRS.